Less sticks, more carrots: New directions for improving food safety in informal markets in low- and middle-income countries - Jaffee, S.; Grace, Delia (International Livestock Research Institute, 2023)
To mark World Food Safety Day 2023, the International Livestock Research Institute (ILRI) and the World Bank co-hosted a webinar to launch a report on new approaches to improving food safety in the informal sector in low- and middle-income countries. The report, New directions for tackling food safety risks in the informal sector of developing countries, authored by Spencer Henson, Steven Jaffee and Shuo Wang, was commissioned by ILRI.